PEMBERDAYAAN EKONOMI BERKELANJUTAN MELALUI SEKTOR PERTANIAN DAN UMKM DI DESA SANGIANG, KEC. MANCAK, KAB. SERANG - Puspitasari, Indah (Jurnal Pengabdian Dinamika, 2023)
Sangiang village is a village located in Mancak District, Serang Regency. It has an area of 293hectares of which 200 hectares are used for agricultural land. About 720 people were employedin the agricultural sector and as many as 55 people were employed as traders. Judging from thedata, it is very supportive to mobilize the community in Sangiang Village, especially MSMEs, andlocal farmers to develop a sustainable economy and motivation in implementing e-commerceplatforms in their marketing. MSME actors in Sangiang village only market their products in thearea. Even so, considering the number of people who visit Sangiang village, such as visitingrelatives or visiting tourist attractions, the customers who place orders have reached outside thearea. Constraints faced by customers who come from outside the region is when placing an order,they must go directly to the store in the village. Furthermore, for local farmers, they haveconducted special training for farmer groups from sub-districts, the government has also helpedto deliver plant seeds to increase the cultivation of plant variations. However, local farmers inSangiang village only process crops raw or simply processed without becoming finished products,this is called unsustainable. From the explanation, the method of implementation carried out inthe service consists of 1) counseling for sustainable economic empowerment in the MSME andagricultural sectors, and 2) motivational counseling to MSME actors related to digitization in themarketing sector. The results of this service have an impact on MSMEs and local farmers asconfirmation of information related to the Sustainable Economy (30% -70%) and motivateMSMEs to encourage the use of e-commerce platforms in the marketing Sector (20% -60%).